Exploitation of coastal and marine resources along Tomini Bay: Livelihood base versus concession rights - Muhammad Obie (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The abundant coastal and marine resources in Tomini Bay are constantly contested between various actors, namely the state, private entities, multilateral institutions, NGOs and the indigenous community, the Bajo Tribe. On the one hand, the Bajo Tribe utilises coastal and marine resources as a livelihood base, while, on the other hand, private entities with concession permits from the state seek to take maximum benefit for their economic prosperity. The research aims to analyse the concession of coastal and marine resources and its implications on the livelihood base of the Bajo Tribe. Livelihood base is defined as a resource or asset that can be utilised to fulfil a community’s need or survival. This research employed a critical theory paradigm with strategy of case study and ethnography. The data collected were qualitative data. Data analyses were conducted using a qualitative approach. The findings revealed that the concession of fishponds and the timber industry has caused Tomini Bay, initially rich in coastal and marine resources, to experience severe environmental damage. This condition has disrupted the livelihood base of the Bajo Tribe. The Bajo Tribe’s livelihood, which is fully dependent on coastal and marine resources, is threatened. The further impact lies in the fact that most Bajo people still live below the poverty line. To maintain the sustainability of coastal and marine resources and ensure the livelihood base of the Bajo Tribe, the utilisation of local wisdom becomes a very astute choice.